Pengaruh kompleksitas pajak, pemeriksaan pajak dan sanksi pajak terhadap kepatuhan wajib pajak - Primasari, Selin; Hendrani, Ai (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This research is meant to test and to find out some factors which is influence the taxpayer compliance. These factors which have been tested in this reaserch are tax complexity, tax audit and tax penalty as independent variables, while taxpayer compliance is the dependent variable. The sample in this research are corporate taxpayers registered at KPP In DKI Jakarta area and obtained using the nonprobability sampling method with the convenience sampling method, the research sample obtained was 64 respondents. The analytical method used is multiple linear regression analysis with statistical application tools. The results of hypothesis testing state that simultaneously the variables of tax complexity, tax audit and tax penalty have an effect on taxpayer compliance. The partial test results show that the variables of tax complexity and tax penalty have no effect on taxpayer compliance. While the tax audit variable has an effect on taxpayer compliance. This research is expected to be a material consideration for interested parties and regulators in an effort to improve taxpayer compliance.